2020
DOI: 10.1186/s12864-020-6734-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals differential immune related genes expression in Ruditapes philippinarum under hypoxia stress: potential HIF and NF-κB crosstalk in immune responses in clam

Abstract: Background: Hypoxia is an important environmental stressor in aquatic ecosystems, with increasingly impacts on global biodiversity. Benthic communities are the most sensitive parts of the coastal ecosystem to eutrophication and resulting hypoxia. As a filter-feeding organism living in the seafloor sediment, Ruditapes philippinarum represents an excellent "sentinel" species to assess the quality of marine environment. In order to gain insight into the molecular response and acclimatization mechanisms to hypoxia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…It was clearly observed that the expression of Mn-ENO significantly increased with the decrease of oxygen concentration ( Figure 6 , p < 0.05), indicating that ENO plays an important role in promoting the anaerobic metabolism in M. nipponense after hypoxia. The rising trend of Mn-ENO in M. nipponense is the same as it is in Ruditapes philippinarum (Adams et Reeve, 1850) [ 27 ]. However, different from R. philippinarum , the expression of Mn-ENO in the hypoxia group was always lower than that in the control group ( Figure 7 , p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was clearly observed that the expression of Mn-ENO significantly increased with the decrease of oxygen concentration ( Figure 6 , p < 0.05), indicating that ENO plays an important role in promoting the anaerobic metabolism in M. nipponense after hypoxia. The rising trend of Mn-ENO in M. nipponense is the same as it is in Ruditapes philippinarum (Adams et Reeve, 1850) [ 27 ]. However, different from R. philippinarum , the expression of Mn-ENO in the hypoxia group was always lower than that in the control group ( Figure 7 , p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…As the research has developed in this field, Mn-LDH and Mn-ENO , which are directly related to lactate, have become more prominent in the field of vision. Mn-LDH reduces pyruvate to lactic acid under hypoxia, preventing the inhibition of glycolysis and ATP synthesis due to the buildup of pyruvate [ 27 ]. It was clearly observed that Mn-LDH decreased with the gradual deterioration of survival status under hypoxia ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Notch family has four transmembrane receptors (Notch1-Notch4) and five ligands (Kadesch, 2004). In the previous studies, fibropellin-1, related to the Notch protein, drastically increased when post chronic hypoxia in the clam Ruditapes philippinarum (Nie et al, 2020) and the NOTCHs were upregulated in Hermodice carunculata under hypoxia (Grimes et al, 2021). Notch signaling was originally identified as a pleiotropic mediator of cell fate in invertebrates, which has recently emerged as an important regulator of immune cells (Radtke et al, 2013;Vanderbeck and Maillard, 2021).…”
Section: Figure 7 |mentioning
confidence: 99%
“…Sequencing technology is widely applied in aquaculture (21)(22)(23)(24). RNA-sequencing technology can effectively reveal genes that are engaged in immune responses and expressed in response to the presence of toxicants or infection (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%